Design and Implementation of Computerized Restaurant Table Booking System - Egigogo, Raji Abdullahi; Tijjani Naniya, Muhammad; Ahmad Abubakar, Abubakar; Almansir Mansir (Ceddi Journal of Information System and Technology (JST), 2024)
The dining landscape has transformed significantly with technological advancements, fundamentally altering how restaurants handle customer reservations. Traditionally, reservations were managed via phone calls or in-person visits, leading to issues like lengthy wait times, uncertain table availability, and limited communication channels. To address these challenges, this paper concentrates on crafting and implementing a Restaurant Table Booking System, aimed at streamlining reservations and enhancing customer experiences. Employing an agile software development methodology ensures flexibility, encourages customer input, and facilitates swift value delivery. Frontend development utilizes HTML, CSS, and Bootstrap for an intuitive user interface, while PHP and MySQL handle backend logic and database operations. Implementation emphasizes reliability and security through the Apache web server.